2019
DOI: 10.1371/journal.pone.0223791
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of post-surgical physical activity in endometrial and ovarian cancer patients

Abstract: ObjectivePhysical activity plays a key role in cancer survivorship. The purpose of this investigation was to (a) describe the post-surgical physical activity trajectories of endometrial (n = 65) and ovarian (n = 31) cancer patients and (b) identify clinical and demographic predictors of physical activity over time.Methods96 participants wore an Actiwatch accelerometer for three days at each of three time points (one week, one month and four months) after surgical intervention for their endometrial or ovarian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Interestingly, despite being a different population, such as having lung cancer, pre‐operative physical activity assessed by the same equipment was similar to patients having enhanced recovery after hip and knee arthroplasty [9, 13]. Similarly, postoperative activity in our cohort of patients was comparable with those after endometrial and ovarian cancer surgery, with very low‐light intensity activities in the first week after surgery [14].…”
Section: Discussionmentioning
confidence: 66%
“…Interestingly, despite being a different population, such as having lung cancer, pre‐operative physical activity assessed by the same equipment was similar to patients having enhanced recovery after hip and knee arthroplasty [9, 13]. Similarly, postoperative activity in our cohort of patients was comparable with those after endometrial and ovarian cancer surgery, with very low‐light intensity activities in the first week after surgery [14].…”
Section: Discussionmentioning
confidence: 66%
“…The value of longer-term postoperative monitoring may also be assessed, possibly through discrete devices or by using wearable devices already used by consumers, which may additionally enhance patient compliance. This is particularly important given the findings of Gorzelitz et al (58) and Carmichael et al (54) who reported impaired activity levels at 4 months and at 28 days postoperatively, respectively. However, the specificity of their relatively well-educated, wealthy female cohort with gynaecologic cancer limits their external validity.…”
Section: Further Researchmentioning
confidence: 87%
“…The recent rise in popularity of commercially available activity trackers provides an opportunity to use these devices to promote PA behavior change, as well as to continuously and objectively measure PA levels as an indicator of intervention adherence [47]. The use of activity trackers may be particularly relevant to promote PA participation in cancer survivors given the relatively low levels of PA that have been recently reported in this population [72,73,74,75]. Indeed, cancer survivors have expressed an interest in using activity trackers to self-monitor PA [76,77,78].…”
Section: Discussionmentioning
confidence: 99%